Timberline, U.S.A.: high-country encounters from California to Maine - Williams, Donald Mace, author; Utah State University Press, publisher (Colorado State University. Libraries, 2003)
As a youth in Denver, Donald Mace Williams developed an affection for high mountain country. After a journalistic career spent mostly on flat lands, he set out to rediscover what was special about country above timberline. He hiked the high alpine in four of America's major ranges-the Rockies, Sierra Nevada, Cascades, and northern Appalachians-and in his narrative of his travels, he tells us what he saw and learned and who he met.
Part I. The Rocky Mountains -- Part II. The Sierra Nevada -- Part III. The Cascades -- Part IV. The Appalachians -- Glossary.
Keywords: Mountains -- United States; Timberline -- United States; Mountain life -- United States; Hiking -- United States; United States -- Description and travel; United States -- History, Local; Williams, Donald Mace -- Travel -- United States